Adoption of artificial intelligence in small and medium-sized enterprises in Spain: The role of competences and skills - Mammadov Huseyn; África Ruiz-Gándara; Luis González-Abril; Isidoro Romero (Amfiteatru Economic, 2024)
This article explores the determinants of the adoption of artificial intelligence (AI) in small and medium-sized enterprises (SMEs) with special attention to the impact of competencies and skills. The research was based on data from a representative sample of SMEs in Spain and used logistic regression econometric analysis. Additionally, the study applied an innovative AI technique, Generative Adversarial Networks (GANs), to balance the data set. The findings indicate that SMEs whose business owners / managers have university degrees or high levels of professional training, those with information technology (IT) experts among their staff, and those providing IT-related training for employees are all more likely to adopt AI. Furthermore, SMEs equipped with management skills in Enterprise Resource Planning (ERP) systems and marketing analytics tools, and SMEs engaged in collaboration with universities and research centres, demonstrate a greater propensity to integrate AI into their operations. The implications of these findings are significant for both business management and public policy. From a managerial perspective, the results underscore the importance of investing in training programmes and initiatives aimed at upgrading the skill set of employees and managers to effectively use AI in business operations. On the policy front, the conclusions suggest an active role for public administrations in promoting the adoption of AI among SMEs by designing initiatives focused on improving key digital competencies.
Keywords: D22; M21; O30; 330; Artificial intelligence; digital competence; digital skill; digitalisation; GAN; information technology; SME